2008
DOI: 10.3200/jach.57.3.291-296
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Screening for Herpes Simplex Virus Among University Students: A Pilot Study

Abstract: Objective-The authors examined the feasibility of conducting serologic testing for the herpes simplex virus 2 (HSV-2) among university students and assessed the psychosocial impact of an HSV-2 diagnosis.Methods-The authors recruited a convenience sample of 100 students (aged 18-39 years) without a history of genital herpes from 1 university between September 2004 and March 2006. Participants received HSV-2 antibody testing by Focus ELISA and Western Blot assays and completed a questionnaire that addressed psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Four studies also compared participants who tested HSV-2 positive with participants who tested HSV-2 negative 25 28 31 32. Three studies compared responses in HSV-2-positive participants with and without a history of genital herpes 27 30 33…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies also compared participants who tested HSV-2 positive with participants who tested HSV-2 negative 25 28 31 32. Three studies compared responses in HSV-2-positive participants with and without a history of genital herpes 27 30 33…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported a negative impact following an HSV-2 diagnosis 25 30. Three months after HSV serological testing, Mark et al 25 found that five HSV-2-seropositive college students reported significantly higher levels of distress than 23 students who tested HSV-2 negative, but found no differences in depression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some U.S. studies have raised concerns about disclosure after serological screening in the absence of pre-existing symptoms or diagnosis, given the low calculated positive predictive value (PPV) of existing enzyme-linked immunosorbent assay (ELISA) tests [22] and the possibility of psychosocial harm. [23] Young adolescents are likely to have a low prevalence of HSV-2 infection,[19, 16] and PPV for all diagnostic tests drops greatly when prevalence is low, resulting in a potentially high rate of false positives.…”
Section: Introductionmentioning
confidence: 99%